2019
DOI: 10.36380/jwpr.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Bedding Materials on the Hematological and Serum Biochemical Parameters of Broiler Chickens

Abstract: The aim of the present study was to determine the effect of different bedding materials on the, hematological and serum biochemical parameters of the broiler chickens. A completely randomized design was employed for the research in which the treatment were five bedding materials (rice hulls, groundnut hulls, wood shaving, sharp sand and control). The treatments were replicated three times each with ten birds in each experimental unit. The birds were brooded for two weeks before the experiment begin. The blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Blood cells play an essential role in the body of animals; for example, they are responsible for the transport of nutrients, the exchange of gases, provide protection to the body and have the ability to synthesize immune bodies [ 36 , 49 , 50 , 51 , 52 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. So, it was found that the introduction of phytobiotics did not significantly affect the morphological parameters of blood, except for the content of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood cells play an essential role in the body of animals; for example, they are responsible for the transport of nutrients, the exchange of gases, provide protection to the body and have the ability to synthesize immune bodies [ 36 , 49 , 50 , 51 , 52 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. So, it was found that the introduction of phytobiotics did not significantly affect the morphological parameters of blood, except for the content of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors demonstrated that probiotics, probiotic and phytobiotic feed additives can have significant influence. Others, on the contrary, claim that these additives do not significantly affect the biochemical parameters of animals [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%